Identity authentication scheme based on identity-based encryption - Ren-ji HUANG; Xiao-ping WU; Hong-cheng LI (网络与信息安全学报)
In large-scale communication nodes network,there are a large number of network nodes and so many types of equipment.So there are problems of certificate management difficulties and resource waste in the tradi-tional PKI cryptosystem.A mutual node authentication scheme based on identity-based encryption,which solved the problem of the digital certificate management in the PKI system by the identity-based encryption and the key escrow problem in identity based cryptograph by splitting the key as well,was designed.At the same time,the introduction of random factor,timestamp and hash algorithm in the authentication protocol prevented various network attacks.Finally,the security and efficiency of the encryption algorithm and the security of the authentication protocol were analyzed,which proved the security and reliability of the authentication scheme.